Dual Role of α-MSH in Colitis Progression: Mediating Neutrophil Differentiation via Bone Marrow - Liao X; Liu H; Li Y; Zhang W; Dai Q; Wei H; Zhou J; Xie X; Zhou H (Journal of Inflammation Research)
Xiping Liao,1,2 Hengqian Liu,3 Yuanyuan Li,1,4 Wei Zhang,1 Qian Dai,1 Haoqi Wei,5 Jianyun Zhou,1 Xia Xie,2 Hongli Zhou1 1Clinical Medical Research Center, The Second Affiliated Hospital, Army Medical University, Chongqing, People’s Republic of China; 2Department of Gastroenterology, The Second Affiliated Hospital, Army Medical University, Chongqing, People’s Republic of China; 3School of Medicine, Chongqing University, Chongqing, People’s Republic of China; 4Hematopoietic Acute Radiation Syndrome Medical and Pharmaceutical Basic Research Innovation Center, Ministry of Education of the People’s Republic of China, Chongqing, People’s Republic of China; 5Department of General Surgery, The PLA 77th Group Army Hospital, Leshan City, People’s Republic of ChinaCorrespondence: Xia Xie, Department of Gastroenterology, The Second Affiliated Hospital, Army Medical University, No. 83 Xinqiao Main Street, Shapingba District, Chongqing, 400037, People’s Republic of China, Email xiexia0128@tmmu.edu.cn Hongli Zhou, Clinical Medical Research Center, The Second Affiliated Hospital, Army Medical University, No. 83 Xinqiao Main Street, Shapingba District, Chongqing, 400037, People’s Republic of China, Email zhouhongli@tmmu.edu.cnBackground: Inflammatory bowel disease (IBD) comprises a group of autoimmune disorders characterized by chronicity and resistance to cure, with an unknown etiology. Recent studies on the brain-gut axis suggest that the central nervous system (CNS), particularly the hypothalamic-pituitary axis (HPA), may play a crucial role in modulating the immune system and influencing disease progression. However, the specific role and mechanism of the HPA in IBD pathogenesis remain unclear. This study aims to investigate the alterations in the HPA and its potential roles during IBD development.Methods: We utilized a dextran sodium sulfate (DSS)-induced colitis model in mice and employed immunofluorescence, real-time quantitative PCR (RT-qPCR), enzyme-linked immunosorbent assay (ELISA), among other techniques, to evaluate the impact of colitis on the HPA. Additionally, we used flow cytometry, adeno-associated virus-mediated gene silence, parabiosis and single-cell RNA sequencing to uncover the specific roles and mechanisms of the HPA in colitis.Results: Our results indicate that colitis activates HPA secretion and increases α-MSH. α-MSH acts on the MC5R present on the surface of hematopoietic stem cells (HSCs) in the bone marrow, altering the bone marrow microenvironment and promoting HSCs proliferation and differentiation into neutrophils. This process enhances the clearance of pathogenic microorganisms during the acute phase of colitis, while inducing sustained inflammatory responses during the remission phase.Conclusion: In summary, our study demonstrates the dual role of HPA activation and α-MSH secretion induced by colitis in the pathogenesis of IBD. These findings offer vital guidance for optimizing personalized treatment of IBD, emphasizing the importance of carefully managing the timing and dosage of α-MSH for its effective clinical application.Keywords: IBD, α-MSH, hematopoietic stem cells, neutrophils, inflammation